SOSIALISASI PROGRAM PENDIDIKAN INKLUSI BERBASIS ICT DAN IMPLIKASINYA TERHADAP PENINGKATAN JUMLAH PESERTA DIDIK BARU DI SD PURBA ADHI SUTA PURBALINGGA - Syaeful Anwar (QALAM: JURNAL PENDIDIKAN ISLAM, 2020)
The general objective of this research is to know the management of education marketing based on information technology at Purba Adhi Suta Elementary School.The specific objectives of the study; (1) to know the conception of education marketing based on information technology (2) management in education marketing strategy based on information technology (3) to know the supporting and obstacle factor of education marketing based on information technology. This research is method qualitative with approach of descriptive. Data collection techniques through in-depth interviews, observation, and document analysis. Data analysis techniques with data reduction steps, data presentation, and draw conclusions. Research result; 1) Based on the concept of marketing mix, the marketing which based on information technology- at Purba Adhi Suta Elementary School is described in the content / product advantages, the methods and media of marketing which based on information technology has attracted the public to become school choice, 2). Supporting factors are physical building, curriculum, human resources, school accreditation, achievement, extracurricular and varied activities, special advantages, marketing strategy especially technology-based information.